PC composite material and preparation method thereof
By using multiple hydrogen bond crosslinked PC resin and carboxylated graphite in PC composite materials, the shortcomings in processing stability and thermal conductivity of existing materials are solved, and a comprehensive improvement of high stability, excellent thermal conductivity and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510390159.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
AI Technical Summary
Existing PC composite materials are prone to dimensional stability problems during processing, insufficient thermal conductivity, and poor compatibility and dispersion of common heat dissipation fillers with PC resins, which affects the mechanical properties and processing stability of the product.
PC resin with multiple hydrogen bond crosslinking capabilities is used as the matrix resin, and combined with carboxylated graphite as the thermal filler, a high-stability and high-strength network structure is formed through hydrogen bonding, thereby improving the processing dimensional stability and thermal conductivity of the product.
It realizes the ideal processing dimensional stability, excellent thermal conductivity and high-strength mechanical properties of PC composite materials, and is suitable for thin-walled electronic device packaging materials.
Smart Images

Figure BDA0005337192810000021 
Figure BDA0005337192810000022 
Figure BDA0005337192810000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and particularly relates to a PC composite material and a preparation method thereof. Background Art
[0002] PC (polycarbonate) has excellent mechanical properties and flame retardancy, so it is very suitable for the field of electronic device packaging. However, when PC is processed, the molecular chain strength is low, and the stress is large. When heated or under long-term processing stress, dimensional shrinkage will occur, ultimately leading to warping. On the other hand, when used for electronic device packaging, the material needs to have sufficient thermal conductivity to avoid oxidation or damage of the device due to untimely heat conduction when heated. However, the intrinsic thermal conductivity of PC is low and needs to be compounded with some heat dissipation fillers. At present, the common heat dissipation fillers have low compatibility with PC and poor dispersion effect, which not only makes it difficult to achieve the expected heat dissipation effect, but may also affect the processing dimensional stability and mechanical strength of the product. Especially in the case of thin-walled product design, the performance drawbacks of the product become more obvious.
[0003] Therefore, people have tried to adopt some processing technologies to optimize the performance of the product. For example, through special processing methods, unidirectionally arranged fiber materials are introduced into PC, so that the thermal conductivity of the product in the unidirectional end is significantly improved, and the processing dimensional stability is good. However, this product cannot be implemented in conventional processing and injection molding equipment and cannot be industrialized. Summary of the Invention
[0004] Based on the defects existing in the prior art, the purpose of the present invention is to provide a PC composite material. In this product, the molecular chains between PC resins can achieve multiple hydrogen bond crosslinking, and finally form a network structure with high stability and high strength. Combined with carboxylated graphite as a heat dissipation filler, it not only has ideal processing dimensional stability, but also has good heat dissipation effect and excellent mechanical properties, and can be used as a thin-walled electronic device packaging material.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A PC composite material, comprising the following components in parts by weight:
[0007] 70 - 90 parts of PC resin, 10 - 30 parts of carboxylated graphite;
[0008] The PC resin contains the following structure:
[0009]
[0010] The carboxyl content of the carboxylated graphite ≥ 1 wt%;
[0011] Among them, relative to the total of the repeating units shown in Structure I and the repeating units shown in Structure II, the proportion m of the repeating units shown in Structure I is 60 to 90 mol%, and the proportion m of the repeating units shown in Structure II is 10 to 40 mol%.
[0012] Preferably, relative to all the repeating units of the PC resin, the total of the repeating units shown in Structure I and the repeating units shown in Structure II is 80 mol% or more and 100 mol% or less.
[0013] More preferably, the total of the repeating units shown in Structure I and the repeating units shown in Structure II relative to all the repeating units of the PC resin is any one or both of the range values of 80 mol%, 85 mol%, 90 mol%, 95 mol%, 99.99 mol%, and more preferably 90 to 99.99 mol%.
[0014] In order to solve the problem of difficult processing of existing common PC composites and the problem of easy occurrence of dimensional stability problems during processing, various processing aids and fillers are introduced into the products. However, such an approach not only has a very limited improvement effect, increases production costs, but also affects the mechanical properties of the products due to problems such as compatibility and dispersibility, especially in the design of thin-walled products; in addition, in order to improve the thermal conductivity of the products, the prior art also implements it by introducing a compound thermal conductivity filler, but this approach also has difficulty in overcoming the problems of compatibility and dispersibility of heterogeneous materials, and the interfacial thermal resistance between the thermal conductivity filler and the PC resin is still relatively high. Therefore, in the technical solution of the present invention, a PC resin having the above structure is used as the matrix resin. This structure has a relatively high intrinsic strength, and the following connection is achieved through hydrogen bonds between multiple repeating structures:
[0015]
[0016] So that the molecular chains in the matrix resin can form a crosslinked network by relying on hydrogen bonds without the action of external forces or modifying components. During the heating process of processing, the movement activity between the molecular chains is greatly reduced, and the stress-bearing strength against the outside world is also greatly improved, and the dimensional stability is significantly improved; on the other hand, in the matrix resin, the present invention also introduces carboxylated graphite as a thermal conductivity filler. Compared with the existing common thermal conductivity fillers, graphite has higher internal lubricity in the PC resin, and at a specific carboxylation degree, graphite can be crosslinked and bound to the PC resin through hydrogen bond action, further improving its dispersibility in the resin. While ensuring that the mechanical properties of the product are maintained at a relatively high level, high dispersibility and high compatibility are achieved, and based on the thermal conductivity effect of graphite itself, the thermal conductivity of the product is significantly improved.
[0017] Preferably, the weight-average molecular weight of the PC resin is 50,000 to 90,000.
[0018] More preferably, the weight-average molecular weight of the PC resin is 65,000 to 70,000.
[0019] Preferably, the weight-average molecular weight of the PC resin can be directly detected by gel permeation chromatography, using dichloromethane as the solvent and a test temperature of 25°C.
[0020] Preferably, in the PC composite material, the weight fraction of the PC resin is one value or the range value of any two of 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts; the weight fraction of the carboxylated graphite is one value or the range value of any two of 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts.
[0021] Preferably, in the PC composite material, the mass percentage content of the PC resin ≥ 70%.
[0022] Preferably, the molar content of the multiple hydrogen bond units in the PC resin ≥ 20%;
[0023] More preferably, the molar content of the multiple hydrogen bond units in the PC resin is 20 - 40%.
[0024] It should be noted that the multiple hydrogen bond units in the PC resin of the present invention can refer to the unit molar content of Structure II.
[0025] The repeating Structure II in the PC resin will form hydrogen bonds with each other. As the unit content of the hydrogen bonds increases, the binding strength between the molecular chains of the PC resin and the overall stability will also increase. Not only the processing dimensional stability of the final product is improved, but the mechanical properties will also be improved; on the other hand, the hydrogen bond force will also reduce the interfacial thermal resistance between the PC resin and the carboxylated graphite, so the thermal conductivity of the product will be further improved.
[0026] Preferably, the PC resin is prepared by copolymerization of reaction monomers;
[0027] More preferably, the reaction monomers of the PC resin include monomer A and monomer B;
[0028] More preferably, the reaction monomers of the PC resin further include triphosgene;
[0029] More preferably, the triphosgene participates in the copolymerization reaction of the PC resin in the form of a solution.
[0030] The monomer A is 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), and the chemical structure of the monomer B is as follows:
[0031]
[0032] More preferably, the molar ratio of the monomer A to the monomer B is (0.18 - 0.25):(0.06 - 0.12);
[0033] More preferably, the steps of the copolymerization reaction are as follows:
[0034] Mix the monomer A and the monomer B in water, then add a metal base, phenol and triethylamine and mix evenly. Add a triphosgene solution to the resulting mixture for reaction. After the reaction is completed, separate the oil phase from the resulting reaction product, wash, filter and dry to obtain the PC resin.
[0035] It should be noted that the PC resin of the present invention can be prepared by the above reaction, but is not limited thereto. This reaction belongs to the conventional monomer copolymerization reaction path well-known to those skilled in the art. The monomer structure is clear. Therefore, those skilled in the art can also adopt other synthetic reaction paths or other monomers for synthesis. The source of the PC resin will not affect the technical effect of the product when the repeating structure meets the limitations of the present invention. Even the PC resin can be replaced by commercially available products with the same configuration.
[0036] Preferably, the carboxyl content of the carboxylated graphite is 1 - 5 wt%, more preferably 2 - 3 wt%.
[0037] The degree of carboxylation of graphite will affect its compatibility and dispersibility in the PC resin, and will also affect the mechanical strength of the product. When the carboxyl content in the carboxylated graphite is within the above preferred range, the comprehensive performance of the product is better.
[0038] Preferably, the test method for the carboxyl content of the carboxylated graphite is thermogravimetric analysis. The specific steps are as follows: Heat the carboxylated graphite dried at 80°C for 12 h in a thermogravimetric analyzer from room temperature to 600°C at a rate of 5°C / min under a nitrogen atmosphere, and measure the weight of the thermal loss of the sample after heating, which is the mass content of carboxyl in the carboxylated graphite.
[0039] Preferably, the mesh number of the carboxylated graphite is 500 - 3000 mesh.
[0040] More preferably, the mesh number of the carboxylated graphite is one of 500 mesh, 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh, 2500 mesh, 3000 mesh or the range value of any two of them.
[0041] More preferably, the mesh number of the carboxylated graphite is 1000 - 2000 mesh.
[0042] When the carboxyl content is the same, the mesh size of the graphite will result in different degrees of hydrogen bonding formation between the carboxyl groups on its surface and the PC resin, and also different dispersibility. When the mesh number of the carboxylated graphite is preferably within the above range, the processing dimensional stability and thermal conductivity of the product are better.
[0043] Preferably, the carboxylated graphite can be prepared by the graphite acid immersion method known to those skilled in the art. The carboxyl content of the product can be adjusted by conventional conditions such as acid concentration, immersion temperature, and immersion time, but it is not limited thereto. Those skilled in the art can also use other methods, such as CVD method, sol method, etc. to carboxylate the graphite. In addition, it can also be directly applied by purchasing commercially available products.
[0044] It should be noted that in the components of the product of the present invention, there is also included 0.01 - 3 parts of processing aids. More preferably, the processing aids include antistatic agents, antioxidants, etc. Those skilled in the art can add them according to actual needs as long as the expected technical effects of the product of the present invention are not affected.
[0045] Another object of the present invention is to provide a method for preparing the PC composite material, comprising the following steps:
[0046] After mixing each component evenly, melt extrude and pelletize in a screw extruder to obtain the PC composite material.
[0047] The preparation method of the PC composite material of the present invention has simple operation steps, does not need to adopt special processes to conduct special design or structural modification on the interior of the product, and can be implemented by using conventional processing and injection molding production lines, and can achieve industrial-scale production.
[0048] Preferably, the temperature range of the screw extruder is set as: 270 - 330 °C, the screw speed is 400 - 600 r / min, and the screw length-diameter ratio is (45 - 50):1.
[0049] Another object of the present invention is to provide the application of the PC composite material in the preparation of electronic and electrical packaging materials.
[0050] Preferably, the electronic and electrical packaging materials include turnover boxes and electronic pallets.
[0051] Another object of the present invention is to provide an electronic and electrical packaging material, comprising the PC composite material of the present invention.
[0052] The PC composite material of the present invention has ideal processing and use properties. During the processing and injection molding process, especially under the thin-wall design, it still has good dimensional stability and does not show warping phenomena. At the same time, its thermal conductivity and mechanical properties are both excellent, fully meeting the performance requirements of electronic and electrical packaging materials.
[0053] The beneficial effects of the present invention are as follows. The present invention provides a PC composite material. In this product, the molecular chains between PC resins can achieve multiple hydrogen bond crosslinkings, ultimately forming a network structure with high stability and high strength. In combination with carboxylated graphite as a heat-conducting filler, it not only has ideal processing dimensional stability, but also has good heat-conducting effect and excellent mechanical properties, and can be used as a packaging material for thin-walled electronic devices. Specific Embodiments
[0054] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples. The purpose is to understand the content of the present invention in detail, rather than a limitation to the present invention. All other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention are all common ordinary reagents and instruments unless otherwise specified.
[0055] Examples 1 to 11
[0056] Embodiments of the PC composite material and its preparation method of the present invention. The component composition of the PC composite material is shown in Table 1.
[0057] The preparation method of the product includes the following steps:
[0058] Mix each component evenly, and then place it into a screw extruder for melt extrusion and pelletization to obtain the PC composite material.
[0059] The temperature zones of the screw extruder are set as follows: Zone 1: 120 °C, Zone 2: 250 °C, Zone 3: 250 °C, Zone 4: 260 °C, Zone 5: 260 °C, Zone 6: 250 °C, Zone 7: 240 °C, Zone 8: 240 °C, Zone 9: 240 °C, Zone 10: 300 °C. The screw rotation speed is 500 r / min, and the length-diameter ratio is 48:1.
[0060] Comparative Examples 1 to 6
[0061] The difference between each comparative example and the example lies only in the types and ratios of components, as shown in Table 2.
[0062] Among the components of each example and comparative example,
[0063] The PC resin 1 is a self-made product, including the following steps:
[0064] (1) 0.1 mol of triphosgene was placed into 200 g of tetrahydrofuran to prepare a solution at -20 °C. Subsequently, 0.4 mol of triethylamine was added and mixed evenly. 0.1 mol of terephthalic dihydrazide was added in 10 portions. Nitrogen was introduced, and the reaction was carried out at -20 °C for 2 h. Subsequently, the temperature was raised to 50 °C and the reaction was carried out for 2 h. After the reaction was completed, filtration was performed, and the filtrate was concentrated by rotary evaporation at 20 °C to obtain intermediate product I;
[0065] (2) 0.3 mol of p-aminophenol was placed into 100 g of tetrahydrofuran to prepare a solution at 60 °C. Under nitrogen protection, intermediate product I was added dropwise. After the addition was completed, the temperature was maintained and the reaction was carried out for 6 h. After the reaction was completed, it was dried by rotary evaporation and washed with ethanol to obtain monomer B:
[0066]
[0067] (3) 0.21 mol of bisphenol A and 41.8 g (i.e., 0.09 mol) of monomer B were mixed in 200 mL of water. At the same time, 0.6 mol of sodium hydroxide, 3 mmol of phenol, and triethylamine with a content of 0.4 wt% of the added materials were added. The mixture was stirred and mixed at 25 °C until the materials were completely dissolved; 100 mL of a dichloromethane solution of triphosgene with a concentration of 0.0001 mol / L was added dropwise to the obtained mixed solution. After the addition was completed, the reaction was carried out at a constant temperature for 60 min. After the reaction was completed, the oil phase was separated, washed with water until the pH was neutral, washed with anhydrous ethanol, precipitated, and dried in a vacuum environment at 80 °C for 6 h to obtain the PC resin 1. The PC resin 1 contains the following repeating structure:
[0068]
[0069] where m = 70% and n = 30%;
[0070] The molar content of the multiple hydrogen bond units in the PC resin 1 is 30%;
[0071] The PC resin 2 is a self-made product. The difference from the PC resin 1 lies in that the molar ratio of bisphenol A and monomer B during polymerization is controlled differently, so that the molar content of the multiple hydrogen bond units in the obtained PC resin is 20%;
[0072] The PC resin 3 is a self-made product. The difference from the PC resin 1 lies in that the molar ratio of bisphenol A and monomer B during polymerization is controlled differently, so that the molar content of the multiple hydrogen bond units in the obtained PC resin is 40%;
[0073] The PC resin 4 is the silicone copolymer PC EXL1414 produced by SABIC;
[0074] The PC resin 5 is TARFLON AG2530 produced by Idemitsu Kosan Co., Ltd. of Japan;
[0075] The PC resin 6 is PC 2407 produced by Covestro Polymer Co., Ltd.
[0076] The carboxylated graphite 1 is a self-made product. The preparation method is as follows: Mix 10 g of graphite powder with a mixed acid of 150 mL of concentrated sulfuric acid / 50 mL of concentrated nitric acid (used to oxidize alkyl groups on the graphite surface to form carboxyl groups), then ultrasonicate at room temperature for 30 min. The obtained graphite dispersion is stirred at 80 °C for 6 h under a nitrogen atmosphere, filtered by suction, and the obtained solid is washed with water until the pH is neutral, and then dried to obtain carboxylated graphite 1. The carboxyl content of the carboxylated graphite 1 is 2.5 wt%. The mesh number of the graphite powder is 1000 mesh, and it is the product YNCM299 produced by Guangdong Yina Technology Co., Ltd.
[0077] The carboxylated graphite 2 is a self-made product. Different from carboxylated graphite 1, the stirring time is 5 h, and the carboxyl content of the carboxylated graphite 2 is 1.5 wt%.
[0078] The carboxylated graphite 3 is a self-made product. Different from carboxylated graphite 1, the stirring time is 8 h, and the carboxyl content of the carboxylated graphite 3 is 3 wt%.
[0079] The carboxylated graphite 4 is a self-made product. Different from carboxylated graphite 1, the mixed acid is 300 mL of concentrated sulfuric acid / 100 mL of concentrated nitric acid, and the stirring conditions are 100 °C and 10 h. The carboxyl content of the carboxylated graphite 4 is 5 wt%.
[0080] The carboxylated graphite 5 is a self-made product. The preparation method is as follows: Mix 10 g of graphite powder with a mixed acid of 150 mL of concentrated sulfuric acid / 50 mL of concentrated nitric acid, then ultrasonicate at room temperature for 30 min. The obtained graphite dispersion is stirred at 80 °C for 10 h under a nitrogen atmosphere, filtered by suction, and the obtained solid is washed with water until the pH is neutral, and then dried to obtain carboxylated graphite 5. The carboxyl content of the carboxylated graphite 5 is 2.3 wt%. The mesh number of the graphite powder is 500 mesh, and it is the product produced by Qingdao Huatai Lubrication Sealing Technology Co., Ltd.
[0081] The carboxylated graphite 6 is a self-made product. The preparation method is as follows: Mix 10 g of graphite powder with a mixed acid of 150 mL of concentrated sulfuric acid / 50 mL of concentrated nitric acid, then ultrasonicate at room temperature for 30 min. The obtained graphite dispersion is stirred at 80 °C for 6 h under a nitrogen atmosphere, filtered by suction, and the obtained solid is washed with water until the pH is neutral, and then dried to obtain carboxylated graphite 6. The carboxyl content of the carboxylated graphite 5 is 2.6 wt%. The mesh number of the graphite powder is 1500 mesh, and it is produced by Nanyang Jinping Mining Co., Ltd.
[0082] The carboxylated graphite 7 is a self-made product, and the preparation method is as follows: Mix 10 g of graphite powder with a mixed acid of 150 mL of concentrated sulfuric acid / 50 mL of concentrated nitric acid, then ultrasonicate for 30 min at room temperature. The obtained graphite dispersion is stirred at 80 °C for 8 h under a nitrogen atmosphere, filtered by suction, and the obtained solid is washed with water until the pH is neutral, and then dried to obtain carboxylated graphite 7; the carboxyl content of the carboxylated graphite 5 is 2.7 wt%; the mesh number of the graphite powder is 2000 mesh, and it is a product produced by Hebei Runhuabang New Material Technology Co., Ltd.;
[0083] The carboxylated graphite 8 is a self-made product. Different from the carboxylated graphite 1, the stirring time is 3 h, and the carboxyl content of the carboxylated graphite 8 is 0.7 wt%;
[0084] The thermal conductive filler 1 is aluminum nitride produced by Shenzhen Institute of Advanced Technology, and the mesh number is 800;
[0085] The thermal conductive filler 2 is boron nitride produced by Qinghe Chaotai Metal Materials Co., Ltd., and the mesh number is 1000.
[0086] Unless otherwise specified, the component raw materials used in each example and comparative example of the present invention are all commercially available raw materials, and the component raw materials used in each parallel experiment are all of the same kind.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091]
[0092] Effect Example 1
[0093] In order to verify the performance of the products of the present invention, the products of each example and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0094] (1) Flexural modulus test: Each product was tested according to ISO178-2019 at a rate of 2 mm / min.
[0095] (2) Thermal conductivity test: Each product was tested according to GB / T 42919.1-2023.
[0096] (3) Dimensional stability test: Each product was tested according to GB / T 17037.4-2003, and finally the dimensional shrinkage rate of the product was calculated. The smaller the shrinkage rate, the higher the dimensional stability of the product.
[0097] The test results are shown in Tables 3 and 4.
[0098] Table 3
[0099]
[0100] Table 4
[0101] Component parts by weight Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Flexural modulus (GPa) 4.8 6.8 6.5 6 6.2 5.8 Thermal conductivity (W / m.K) 0.64 0.47 0.55 0.85 0.78 0.79 Dimensional shrinkage rate (%) 0.6 0.9 0.9 0.8 0.6 0.9
[0102] As can be seen from Table 3 and Table 4, in the product of the present invention, due to the crosslinking network of the PC resin itself and the compounding effect of carboxylated graphite, the product not only has good processing dimensional stability, and the dimensional shrinkage rate can be maintained within 0.4%, but also has a relatively high thermal conductivity, which can reach 0.5 W / m·K or above. In addition, the compounding of the two does not affect the mechanical properties of the product. When the flexural modulus reaches 4.2 GPa or above, it fully meets the basic mechanical use requirements of electronic and electrical packaging materials.
[0103] As can be seen from Example 1, Examples 4 to 5, and Comparative Examples 4 to 6, in the PC composite material of the present invention, the selection of PC resin is very crucial. Due to the setting of the special repeating structure, the molecular chains in the matrix resin can form a crosslinking network by relying on hydrogen bonds without the action of external forces or modifying components. During the heating process of processing, the movement activity between molecular chains is greatly reduced, and the stress-bearing strength against the outside world is also greatly improved, and the dimensional stability is significantly improved. On the other hand, in the matrix resin, the present invention also introduces carboxylated graphite as a thermal conductive filler. Compared with common existing thermal conductive fillers, graphite has higher internal lubricity in PC resin, and at a specific degree of carboxylation, graphite can be crosslinked and bound to PC resin through hydrogen bond action, further improving its dispersibility in the resin. While ensuring that the mechanical properties of the product are maintained at a relatively high level, high dispersibility and high compatibility are achieved. Selecting a conventional PC resin can achieve similar mechanical properties or thermal conductivity, but the dimensional shrinkage rate of the product cannot meet the standard. Further, when the molar content of multiple hydrogen bond units in the PC resin gradually increases, not only the dimensional shrinkage rate of the product is further reduced, but also the tensile strength and thermal conductivity of the product are improved to a certain extent.
[0104] As can be seen from Example 1, Examples 6 to 8, and Comparative Example 1, when the degree of carboxylation in graphite is insufficient, graphite cannot be crosslinked and bound to the resin due to hydrogen bond action, and graphite cannot achieve good dispersibility and compatibility. Therefore, not only the dimensional shrinkage rate of the product is relatively high, but also the tensile strength and thermal conductivity are relatively low. As the degree of carboxylation gradually increases, the various properties of the product are significantly improved, especially the dimensional shrinkage rate, which can reach a minimum of 0.2%. However, as the degree of carboxylation further increases, the dimensional shrinkage rate of the product will show a certain increase. When the carboxyl content of carboxylated graphite is 2-3 wt%, the comprehensive performance of the product is better.
[0105] In addition, when the degree of carboxylation is similar, the mesh number of graphite will also have a certain impact on the performance of the product. As can be seen from Examples 1 and 9-11, due to the different mesh numbers of graphite, the probability of the carboxyl groups on its surface forming hydrogen bonds with the resin is also different, which in turn leads to different dispersibility and compatibility of the product. As the mesh number increases, the graphite particle size becomes smaller and smaller, the tensile strength of the product gradually increases, and based on the improvement of dispersibility and compatibility, the thermal conductivity and dimensional stability of the product are also improved. However, when the mesh number of graphite further increases, the dispersibility of the product is affected to a certain extent, and the thermal conductivity and dimensional stability of the product decrease to a certain extent. Therefore, when the mesh number of carboxylated graphite is 1000-2000 meshes, the comprehensive performance of the product is obviously better. However, in comparison, all these products are better than the products prepared with other filler types described in Comparative Examples 2 and 3 with similar dimensions.
[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A PC composite material, characterized in that: The composition comprises the following components in parts by weight: 70-90 parts of PC resin, 10-30 parts of carboxylated graphite; The PC resin comprises the following structure: wherein, relative to the sum of the repeating units represented by structure I and the repeating units represented by structure II, the ratio m of the repeating units represented by structure I is 60 to 90 mol%, and the ratio m of the repeating units represented by structure II is 10 to 40 mol%; The carboxyl content of the carboxylated graphite is ≥ 1 wt %.
2. The PC composite material according to claim 1, characterized in that: The weight average molecular weight of the PC resin is 50,000 to 90,000.
3. The PC composite material according to claim 1, characterized in that: The molar content of the multiple hydrogen bonding units in the PC resin is ≥20%; preferably, the molar content of the multiple hydrogen bonding units in the PC resin is ≥30%.
4. The PC composite material according to claim 1, characterized in that: The carboxyl content of the carboxylated graphite is 1 to 5 wt %; preferably, the carboxyl content of the carboxylated graphite is 2 to 3 wt %.
5. The PC composite material according to claim 1, characterized in that: The mesh number of the carboxylated graphite is 500 to 3000 meshes.
6. The method for preparing the PC composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: After the components are uniformly mixed, they are melt-extruded and granulated in a screw extruder to obtain the PC composite material.
7. Use of the PC composite material according to any one of claims 1 to 5 in the preparation of electronic and electrical packaging materials.
8. An electronic and electrical packaging material, characterized in that: The PC composite material comprises the PC composite material according to any one of claims 1 to 5.
9. The electronic and electrical packaging material according to claim 8, characterized in that: The electronic and electrical packaging materials include turnover boxes and electronic pallets.